Effects of dietary macronutrients on serum urate: results from the OmniHeart trial. Issue 6 (1st March 2021) - Belanger, Matthew J; Wee, Christina C; Mukamal, Kenneth J; Miller, Edgar R; Sacks, Frank M; Appel, Lawrence J; Shmerling, Robert H; Choi, Hyon K; Juraschek, Stephen P
ABSTRACT: Background: Dietary recommendations to prevent gout emphasize a low-purine diet. Recent evidence suggests that the Dietary Approaches to Stop Hypertension (DASH) diet reduces serum urate while also improving blood pressure and lipids. Objective: To compare the effects of DASH-style diets emphasizing different macronutrient proportions on serum urate reduction. Methods: We conducted a secondary analysis of the Optimal Macronutrient Intake Trial to Prevent Heart Disease feeding study, a 3-period, crossover design, randomized trial of adults with prehypertension or hypertension. Participants were provided with 3 DASH-style diets in random order, each for 6 wk. Each DASH-style diet emphasized different macronutrient proportions: a carbohydrate-rich (CARB) diet, a protein-rich (PROT) diet, and an unsaturated fat-rich (UNSAT) diet. In the PROT diet, approximately half of the protein came from plant sources. We compared the effects of these diets on serum urate at weeks 4 and 6 of each feeding period. Results: Of the 163 individuals included in the final analysis, the mean serum urate at baseline was 5.1 mg/dL. Only the PROT diet reduced serum urate from baseline at the end of the 6-wk feeding period (–0.16 mg/dL; 95% CI: –0.28, –0.04; P  = 0.007). Neither the CARB diet (–0.03 mg/dL; 95% CI: –0.14, 0.09; P  = 0.66) nor the UNSAT diet (–0.01 mg/dL; 95% CI: –0.12, 0.09; P  = 0.78) reduced serum urate from baseline. The PROT diet lowered serum urate by 0.12 mg/dL (95% CI: –0.20, –0.03; P  = 0.006) compared with CARB and by 0.12 mg/dL (95% CI: –0.20, –0.05; P  = 0.002) compared with UNSAT. Conclusions: A DASH-style diet emphasizing plant-based protein lowered serum urate compared with those emphasizing carbohydrates or unsaturated fat. Future trials should test the ability of a DASH-style diet emphasizing plant-based protein to lower serum urate and prevent gout flares in patients with gout. This trial was registered at clinicaltrials.gov as NCT00051350.